2023
DOI: 10.3390/ijms24065321
|View full text |Cite
|
Sign up to set email alerts
|

PPAR Alpha Activation by Clofibrate Alleviates Ischemia/Reperfusion Injury in Metabolic Syndrome Rats by Decreasing Cardiac Inflammation and Remodeling and by Regulating the Atrial Natriuretic Peptide Compensatory Response

Abstract: Metabolic syndrome (MetS) is a cluster of factors that increase the risk of developing diabetes, stroke, and heart failure. The pathophysiology of injury by ischemia/reperfusion (I/R) is highly complex and the inflammatory condition plays an important role by increasing matrix remodeling and cardiac apoptosis. Natriuretic peptides (NPs) are cardiac hormones with numerous beneficial effects mainly mediated by a cell surface receptor named atrial natriuretic peptide receptor (ANPr). Although NPs are powerful cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 73 publications
0
3
0
1
Order By: Relevance
“…An animal study has shown that clofibrate can improve oxidative stress and neuroinflammation caused by the exaggerated production of lipid peroxidation products [ 54 ]. Clofibrate can activate peroxisome-proliferator-activated receptors (PPAR) α, inhibit the activation of the NF-κB signaling pathway and the production of interleukin (IL)-6, exerting an anti-inflammatory effect [ 55 , 56 ]. Additionally, a recent animal study indicated the upregulation of astrocytic activation and glial fibrillary acidic protein (GFAP) expression in the trigeminal nucleus caudalis (TNC) in migraine mice model induced by recurrent dural infusion of inflammatory soup (IS).…”
Section: Discussionmentioning
confidence: 99%
“…An animal study has shown that clofibrate can improve oxidative stress and neuroinflammation caused by the exaggerated production of lipid peroxidation products [ 54 ]. Clofibrate can activate peroxisome-proliferator-activated receptors (PPAR) α, inhibit the activation of the NF-κB signaling pathway and the production of interleukin (IL)-6, exerting an anti-inflammatory effect [ 55 , 56 ]. Additionally, a recent animal study indicated the upregulation of astrocytic activation and glial fibrillary acidic protein (GFAP) expression in the trigeminal nucleus caudalis (TNC) in migraine mice model induced by recurrent dural infusion of inflammatory soup (IS).…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory factors are direct inducers of atrial fibrosis, suggesting that inhibiting myocardial inflammation could be a viable strategy to reverse atrial fibrosis. The anti-inflammatory effect of ANP has been observed in various animal models, showing alleviation of inflammation in tissues like the pancreas, colon, and myocardium [37][38][39]. Clinical studies have indicated that ANP infusion can mitigate spontaneous inflammation following myocardial infarction, reducing ventricular fibrosis and counteracting adverse ventricular remodeling [19].…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, fenofibrate supplementation produced no noticable hydropic changes in liver tissue sections. PPAR alpha agonists are known to suppress inflammatory events via the NF-κB pathway and inhibit ROS production [23,24], Therefore, it is possible that damaging effect of hydrogen peroxide by-product of peroxisomal oxidation activity might have been served as an offset through antioxidant and antiinflammatory action of fibrates.…”
Section: Discussionmentioning
confidence: 99%